2022
DOI: 10.1200/jco.21.01991
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Lymphocyte Count Predicts Benefit From Concurrent Chemotherapy With Radiotherapy in Oropharyngeal Cancer

Abstract: PURPOSE There is a need to refine the selection of patients with oropharyngeal squamous cell carcinoma (OPSCC) for treatment de-escalation. We investigated whether pretreatment absolute lymphocyte count (ALC) predicted overall survival (OS) benefit from the addition of concurrent chemotherapy to radical radiotherapy. PATIENTS AND METHODS This was an observational study of consecutive OPSCCs treated by curative-intent radiotherapy, with or without concurrent chemotherapy (n = 791) with external, independent val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…In this study, albumin was associated with OS and PFS, and patients with lower albumin had a poor prognosis. Lymphocytes can strengthen the immune surveillance ability and suppress the proliferation, invasion, and metastasis of tumour cells and have been used to predict the prognosis of patients with many types of tumours, such as oropharyngeal cancer, melanoma, and skin cancer [ 21 , 22 , 23 , 24 ]. Serum monocyte levels can reflect the formation of tumour-associated macrophages (TAMs) in the tumour microenvironment [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, albumin was associated with OS and PFS, and patients with lower albumin had a poor prognosis. Lymphocytes can strengthen the immune surveillance ability and suppress the proliferation, invasion, and metastasis of tumour cells and have been used to predict the prognosis of patients with many types of tumours, such as oropharyngeal cancer, melanoma, and skin cancer [ 21 , 22 , 23 , 24 ]. Serum monocyte levels can reflect the formation of tumour-associated macrophages (TAMs) in the tumour microenvironment [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The studies looking at predictivity of ALC in head and neck have been more discordant. When looking at oropharyngeal cancer, lower pretreatment ALC was prognostic for worse overall survival, but studies in nasopharyngeal carcinoma (NPC) showed that pretreatment ALC was not predictive marker for survival 12,13,18 . However, the NPC studies did show that treatment‐related lymphopenia, high NLR, and high platelet lymphocyte ratio (PLR) was associated with worse survival 12,13 …”
Section: Discussionmentioning
confidence: 99%
“…When looking at oropharyngeal cancer, lower pretreatment ALC was prognostic for worse overall survival, but studies in nasopharyngeal carcinoma (NPC) showed that pretreatment ALC was not predictive marker for survival. 12,13,18 However, the NPC studies did show that treatment-related lymphopenia, high NLR, and high platelet lymphocyte ratio (PLR) was associated with worse survival. 12,13 This study evaluates the prognostic value of pretreatment ALC in oral cavity cancers with regards to both recurrence and survival.…”
Section: Association Of Alc With Death and Recurrencementioning
confidence: 99%
“…In PACIFIC, patients derived a PFS benefit from the anti-PD-1 antibody durvalumab after chemoradiotherapy (HR 0.55, 95% CI 0.45-0.68), which was more pronounced in those with PD-L1-high tumours (HR 0.41, 95% CI 0.26-0.65) 146 . The pretreatment absolute lymphocyte count has prognostic value as a biomarker of immune function and also predicts for benefit from the addition of radiotherapy to chemotherapy in oropharyngeal carcinoma 151 and to immunotherapy in various solid tumour types 152 . Although this area of investigation is currently very active, at the time of writing none of the above immune biomarkers has been translated into clinical practice 153 .…”
Section: Review Articlementioning
confidence: 99%